The formation and assembly history of the Milky Way revealed by its globular cluster population - Kruijssen, Diederik; Reina-Campos, Marta (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. We use the age-metallicity distribution of 96 Galactic globular clusters (GCs) to infer the formation and assembly history of the Milky Way (MW), cul